Tectonic and tectosedimentary characteristics of the Rincón Blanco halfgraben: A synthesis - Barredo, S. (2010)
The Gondwana margin contained some Triassic basins that together constitute a regionally northwest-trending extensional system. The Cuyana rift Basin is internally composed of a family of hemigrabens filled with thick piles of sedimentary clastic and epiclastic rocks that can reach more than three thousand meters. In particular the Rincón Blanco sub-basin, one of the northernmost depocenter of this rift, is bounded by a linked through-going normal fault that usually displays an en-échèlon map view. Along strike existence of discrete depocenters and alternation of sedimentary wedges of different types suggest a linkage origin for some of them separated by a transfer zone. The infilling was strongly controlled by tectonics which in term produced distinctive features along the whole sedimentary sequence. An immediate consequence of this latter is that the architecture of the fill resulted from the geometry and the displacement of the bounding normal faults. Using lithology and structural data the infilling was subdivided into packages of genetically linked units bounded by regional extended surfaces. Hence, three depositional sequences or tectono- stratigraphic units separated by regional unconformities have been recognized. They were interpreted as a result of a major reactivation of the extensional system that could have evolved along strike as segments of fault that linked together and/or as laterally propagating faults. Using these basic concepts it was possible to reconstruct the geometry and the history of the infilling of the east margin of the hemigraben, buried under several backthrusts. Additionally, it could be possible to separate a sequence of rock, the Marachemill Unit, from the Rincón Blanco Group and to understand their tectonosedimentary relationships.